Outreach library services for distance learners - Jagannathan Neela; Kanjilal Uma; Panda Santosh (New Delhi Viva Books, 2004)
This volume strings together some of the well known distance educators across nations to deliberate on the issues, concerns and challenges of the library services including document delivery in portable document format(pdf), access to digital libraries
Keywords: Distance education; Distance learners; Library services